1999
DOI: 10.1038/sj.gt.3300891
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral delivery of IL-12 gene by polyvinyl polymeric vector system to murine renal and colon carcinoma results in potent antitumor immunity

Abstract: We have utilized a nonviral, polymeric interactive non-conoptimal doses of 24 and 48 g, respectively. While polydensing (PINC) gene delivery system to deliver IL-12 to morphonuclear cells (PMNs) were partially involved in the two different types of murine tumors, an immunogenic development of the antitumor immune response elicited by renal cell carcinoma, Renca, and a non-immunogenic IL-12/PVP treatment, CD8 + T cells were found to be the colon cell carcinoma, CT26. The delivery of IL-12/polyvinyl primary effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 34 publications
2
55
0
Order By: Relevance
“…The elimination of CD4 + cells from mice bearing CT-26 colon adenocarcinoma dramatically potentiates antitumor activity of IL-12, and depletion of CD4 + cells has significantly increased the survival of Renca -and CT26 -bearing mice. 12,21 Taken together, these findings indicate that the decreased CD4 + cells we observed in our study may also contribute to the antitumor activity in our model.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The elimination of CD4 + cells from mice bearing CT-26 colon adenocarcinoma dramatically potentiates antitumor activity of IL-12, and depletion of CD4 + cells has significantly increased the survival of Renca -and CT26 -bearing mice. 12,21 Taken together, these findings indicate that the decreased CD4 + cells we observed in our study may also contribute to the antitumor activity in our model.…”
Section: Discussionsupporting
confidence: 76%
“…The structure of the construct, which contains both subunits of IL -12, is depicted in their publication. 12 The backbone elements of this construct are described in our previous publication. 13 The control construct is the result of deletion of IL -12 cDNA.…”
Section: Experimental Animalsmentioning
confidence: 99%
“…Furthermore, nonviral vectors may be good clinical options because they may be more efficient and less labor intensive than viral vectors, although the present gene transfection efficiencies still need to be improved. Recently, nonviral gene delivery systems with polyvinylpyrrolidone (PVP), 16 poly[a-(4-aminobutyl)-L-glycolic acid] (PAGA), 17,18 and water-soluble lipopolymers (WSLP) 19 have been developed and reported. However, the best method for intratumoral delivery of the IL-12 gene remains to be determined.…”
mentioning
confidence: 99%
“…Earlier reports have shown that IL-12 acts independently to promote a Th1 type response against tumor growth and metastasis, as well as by inducing other anti-tumor cytokines such as IFN-␥, TNF-␣ and granulocyte-macrophage colony-stimulating factor (GM-CSF) which can act synergistically to reduce and in some cases completely eradicate the tumor. 3,7,[19][20][21] There is evidence that IL-12 inhibits angiogenesis and induces apoptosis, as well as extensive necrosis in murine tumor. 22 Our studies show that use of PAGA/pmIL-12 complexes significantly enhances the levels of IL-12 p70 production compared with naked pmIL-12 and 5% (w/v) glucose-injected groups ( Figure 1), which would reduce the potential of tumor growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…7 Although these systems produced mIL-12 and mIFN-␥, the levels of transgene expression and tumor regression were low, possibly due to little protection of plasmid DNA by PVP. Moreover, no comparison was made between naked pmIL-12 in saline and PVP/pmIL-12-based formulations for transgene expression and tumor regression.…”
Section: Introductionmentioning
confidence: 99%